(3Whb GdUGOM GrdeaUd HLhgQ GrdnHnjGf GrdnhGpVMs - (3GdchcHGfj Knqe GdUfYGfj, ojhoSa Hf Ydj Hf GdgGOj (B, (3J (B1116 (3g`s
(3ChdgG (B:s
(3CMeO ef Whbfj HGdEfYGe agPG QhV COH CKeQJ ChQGbg GdTcQ hUOMJ GdScQ hGMJhi Ydi eG bjd ef GdfXe GdHOjY aj GdMeGFe hGdKfGA Ydi ef CKHJ aj CYfGbgG ef fXeg ejGSe s
(3BNQgG (B:s
(3hLjg GdOjf YHO GdQMef Hf YHO GdgGOj GSJhRQg ehdGfG Sja GdNdGaI hEPG bO HdZ HfG gPG GdSdhc Edi EjQGO gPG GdSdhc (B, (3ajMSf Cf fahR HMSf GdNJGe ef MOjK NGJe GdCfHjGA MOKfj CNj Gdabjg VjGA GdOjf ESeGYjd Jes
(3fSN HYfGjI (B: (3CejQ GdeDefjf EHQGgje Hf eMeO Hf GdMSjf (B( (3ef CeQGA Gdjef (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\242s
(3gOjI GdYGQajf (B2\567s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdCOHs